The relationship between physical exercise and depressive symptoms in college students: the mediating role of rumination - Zhu, Bei; Liu, Qing; Jia, Shuqi; Wang, Xing; Man, Qin (Frontiers in Psychiatry, 2024)
ObjectiveThis study aims to explore the correlation between physical exercise, rumination, and depressive symptoms in college students, as well as to investigate the potential pathways through which physical exercise may impact depressive symptoms. This exploration offers valuable insights for the development of clinical exercise interventions.MethodsA cross-sectional study design was employed, with 2,902 participants recruited via convenience sampling. Structural equation modeling was utilized to explore the relationship between physical exercise and depressive symptoms in college students.Results1) Statistically significant differences were observed between depressed and non-depressed college students in terms of rumination, symptom rumination, reflective pondering, and compulsive meditation (all P < 0.05); 2) Physical exercise was found to negatively predict symptom rumination (B=-0.083, P<0.001), compulsive thinking (B=0.034, P>0.05), reflective pondering (B=-0.038, P<0.01), and BDI-II scores (B=-0.103, P<0.001). Symptom rumination positively predicted BDI-II scores (B=0.648, P<0.001), while compulsive thinking and reflective pondering were found to predict BDI-II scores positively (B=0.028, P>0.05) and negatively (B=-0.041, P>0.05), respectively. 3) Physical exercise exerted a direct effect of 59.09% on BDI-II scores (B: -0.065, 95% CI -0.104, -0.028), indicating that higher levels of physical exercise were associated with lower BDI-II scores. The coefficients for duration, intensity, and frequency were statistically significant (all P < 0.05), with intensity and frequency exhibiting higher path coefficients. Rumination, as a latent variable, mediated 40.91% of the indirect effect (B: -0.045, 95% CI -0.077, -0.015), with symptom rumination emerging as a statistically significant pathway (P < 0.05).ConclusionRumination may mediate the relationship between physical exercise and depressive symptoms, with varying mediating effects across different dimensions of rumination. The intensity and duration of physical exercise exert a stronger influence.